Manajemen MQTV dalam Syiar Dakwah Melalui Platform Youtube - Ryan Rahmat; Ida Afidah; Chairiawaty (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. Today’s youth are ignorant of the social issues around them. Promiscuity, juvenile delinquency,ldruglabuse, and sex are all things that have affected modern teenagers. In the midst of a moral crisis,lthe Islamic Boarding School is a place for moral development. The purpose of the study was to find out the programs in the Boarding School to improve the morals of itslstudents, to find out the role of the board in improving the morals oflits students, and to find out the supportingland inhibiting factors used by the board in improving the morals oflthe students. This research uses descriptivenqualitative methods. Islamic Boarding School programs in improving the morals of its students, namely the program of studying book of akhakullbanin and studying shariyahan activities. The managementlhelps programs and activities that aim to improve akhlakul karimah. Thus, the role of the management is included in the active role category, where hey help their students improve their morals through various activities and supervision. Supporting factors from the santri guardian, and providing comfortable facilities. The inhibiting factors are the students' own culture. Abstrak. This study focuses on MQTV Management in Spreading Da'wah through the YouTube Platform. This study aims to determine the programs broadcast on MQTV and how MQTV management manages spreading da'wah through YouTube. The method used is a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation. This study found that the programs on MQTV consist of various programs such as Kajian Aa Gym, Living With Qur'an, Smart Moms, Cerita Muslimah, Ustadz Jaga, Dibalik Layar, and Dakwah Zilenial. MQTV management has implemented George R. Terry's management functions which include planning, organizing, implementing, and supervising. Currently, the MQTV Official YouTube channel has more than 54.1 thousand subscribers and has reached the monetization stage. The results of this study are that MQTV management in spreading da'wah through the YouTube platform has been running well and effectively, implementing management functions ranging from planning to supervision. Periodic evaluation and statistical analysis are carried out to improve content quality.